Electronic health information systems for public health care in South Africa: a review of current operational systems - Wright, Graham; O'Mahony, Don; Cilliers, Liezel (Journal of Health Informatics in Africa, 2017)
Background and Purpose: The South African eHealth Strategy was published in 2012 and acknowledges that health information systems should be used to strengthen the public health care system in the country. While the benefit of electronic health information systems has been documented in the literature, the implementation of these systems in public health care in South Africa remains limited. Currently, patient data is still manually recorded in the patient’s file, while data required for monitoring and evaluation purposes is hand written by the nurses in registers, aggregated and only the results entered into electronic health information systems for analysis.Methods: The objective of the paper is to review existing electronic health information systems in public health care in South Africa in terms of their role and focus on health care. A qualitative approach was undertaken to identify the role of health information systems that are most prevalent in public health care in South Africa.Results: The results indicate that the most common role of health information systems include support for  clinical care, e.g. radiology and pathology, as well as monitoring, evaluation and administration purposes. While some systems do capture limited clinical information, there seems to be few systems that support patient centred clinical care.Conclusions: The recommendation of the paper is that the role of health information systems should be expanded to support direct patient care and improve health outcomes for individuals.